Preoperative routine evaluation of bilateral adrenal glands by endoscopic ultrasound and fine-needle aspiration in patients with potentially resectable lung cancer - Uemura, S.; Yasuda, I.; Kato, T.; Doi, S.; Kawaguchi, J.; Yamauchi, T.; Kaneko, Y.; Ohnishi, R.; Suzuki, T.; Yasuda, S.; Sano, K.; Moriwaki, H. (Endoscopy, 2013)
Background and study aims: The aim of the current study was to assess the detection rate of the right adrenal gland and the diagnostic ability of endoscopic ultrasound (EUS) and fine-needle aspiration (FNA) for the diagnosis of adrenal metastasis in potentially resectable lung cancer.Patients and methods: This retrospective cohort study included a consecutive series of 150 patients undergoing EUS/EUS – FNA for staging of lung cancer. The detection rate of the right adrenal gland by EUS and the diagnostic accuracies of computed tomography (CT), positron emission tomography-CT (PET-CT), and EUS/EUS – FNA for the diagnosis of adrenal metastasis were evaluated.Results: The right adrenal gland was visualized by EUS in 131 patients (87.3 %); the left adrenal gland was visualized in all patients. Findings suggestive of metastasis in either one of the adrenal glands or in both were observed in 6 patients (4.0 %) by CT, in 5 patients (3.3 %) by PET-CT, and in 11 patients (7.3 %) by EUS. EUS – FNA was performed simultaneously in the 11 patients, and in 4 patients the diagnosis of metastasis was established. The accuracy for the diagnosis of adrenal metastasis was 100 % for EUS/EUS – FNA, 96.0 % for CT, and 97.0 % for PET-CT (P = 0.1146). Conclusions: As well as the left adrenal gland, the right adrenal gland was also usually visible by EUS. EUS/EUS – FNA provided an accurate diagnosis of adrenal metastasis, although the prevalence of adrenal metastasis was relatively low in these patients with potentially resectable lung cancer.